Evaluation Of Surgical Induced Astigmatism In 2.75 Mm Temporal Clear Corneal Incision After Phacoemulsification - Titiek Ernawati; Kevin Anggakusuma Hendrawan; Okky Imanuel Samantha; Kevin Samsudin (JURNAL WIDYA MEDIKA, 2020)
Background : Cataract is still one of the eye health problem. Blindness due to cataract can be prevented with cataract surgery so the vision can be corrected. Cataract surgery have huge development and now phacoemulsification is used widely. Surgically induced astigmatism is one of many tools to evaluate the success of cataract surgery. Surgically induced astigmatism will affect visual acuity. There are many factors contributing the incident of surgically induced astigmatism such as size of incision, location of incision, and pre surgery astigmatism. Objective : to analyze surgically induced astigmatism after cataract surgery with 2.75 mm temporal clear corneal incision phacoemulsification technique. Material and Methods : Cross-sectional studies has been conducted on 92 subject. Astigmatism were evaluated in every subject before and after cataract surgery. Surgically induced astigmatism were evaluated by evaluating keratometry before and after cataract surgery. Comparative statistics were used to evaluate comparison between variable. Result : The mean pre-operative astigmatism were 0.88 D, and mean of post-operative astigmatism were 0.81 D. Decreased in post-operative astigmatism found in 41 subject (44.6%), increased in 31 subject (33.7%), and 20 subject (21.7%) had no changes in astigmatism. There was no statistically significant difference between pre and post-operative astigmatism (p = 0.214). Conclusion : There was no significant surgically induced astigmatism in patients undergo phacoemulsification with 2.75 mm temporal clear corneal incision.